Class I HDAC inhibitors enhance antitumor efficacy and persistence of CAR-T cells by activation of the Wnt pathway - Zhu, Meng; Han, Yingli; Gu, Tianning; Wang, Rui; Si, Xiaohui; Kong, Delin; Zhao, Peng; Wang, Xiujian; Li, Jinxin; Zhai, Xingyuan; Yu, Zebin; Lu, Huan; et al. (Cell reports (Cambridge), 2024)
Epigenetic modification shapes differentiation trajectory and regulates the exhaustion state of chimeric antigen receptor T (CAR-T) cells. Limited efficacy induced by terminal exhaustion closely ties with intrinsic transcriptional regulation. However, the comprehensive regulatory mechanisms remain largely elusive. Here, we identify class I histone deacetylase inhibitors (HDACi) as boosters of CAR-T cell function by high-throughput screening of chromatin-modifying drugs, in which M344 and chidamide enhance memory maintenance and resistance to exhaustion of CAR-T cells that induce sustained antitumor efficacy both in vitro and in vivo. Mechanistically, HDACi decrease HDAC1 expression and enhance H3K27ac activity. Multi-omics analyses from RNA-seq, ATAC-seq, and H3K27ac CUT&Tag-seq show that HDACi upregulate expression of TCF4, LEF1, and CTNNB1, which subsequently activate the canonical Wnt/β-catenin pathway. Collectively, our findings elucidate the functional roles of class I HDACi in enhancing CAR-T cell function, which provides the basis and therapeutic targets for synergic combination of CAR-T cell therapy and HDACi treatment. [Display omitted] •Screening of chromatin-modifying drugs identifies class I HDACi as boosters of CAR-T cells•Class I HDACi enhance persistence and in vivo antitumor efficacy of CAR-T cells•Class I HDACi decrease HDAC1 expression and enhance H3K27ac activity•Multi-omics reveal class I HDACi activating the Wnt pathway in CAR-T cells In this study, Zhu et al. show that class I HDAC inhibitors, particularly M344 and chidamide, markedly improve persistence and antitumor efficacy of CAR-T cells by regulation of the HDAC1-H3K27ac axis and activation of the canonical Wnt/β-catenin signaling pathway.